Drug inhibition of bacterial two-component regulatory systems - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2018)
There are several ways to adapt and increase the chances of survival of microorganisms. Specific systems involved in the recognition of external changes and the organization of the corresponding reaction of the microorganism are called bacterial sensory systems. Bacterial sensory or regulatory systems can be activated by both chemical and mechanical triggers. These bacterial regulatory systems are divided into four main groups: 1) a group of quorum sensing systems; 2) a group of single-molecule autonomous regulators; 3) a group of regulatory RNAs that play a crucial role in regulating the activity of transcription and translation in eukaryotes and bacteria; 4) a group of two-component systems (TCS), which are the most common bacterial regulatory systems. As a result of excitation of the sensory kinase, the signal chains associated with TCS lead to the activation of expression of the virulence factor genes. Therefore, drug suppression of TCS can reduce the level of bacterial virulence and contribute to the resolution of the infectious process. Anti-TCS drugs are promising antimicrobial drugs, and in the near future they will take a worthy place in the therapy of infectious inflammatory diseases of the respiratory tract caused by antibiotic-resistant bacterial strains.